Plural policing, the public good, and the constitutional state: an international comparison of Austria and Canada – Ontario. (4th May 2018) - van Stokkom, Bas; Terpstra, Jan
ABSTRACT: For the past two or three decades many jurisdictions have experienced a pluralisation of policing. In addition to the regular public police, in most countries new providers have become involved in policing public and semi-public places. This paper deals with the differences in the ways that plural policing and its consequences are defined and assessed in different countries. The paper focuses on two countries that differ considerably in the impact of neoliberalism, Austria and Canada – Ontario. In these countries different discourses are used to assess plural policing and its potential negative impact. In Canada the public good is the central concept in discussions of plural policing. This often refers to instrumental goals such as value for money and service delivery to consumers. In Austria plural policing is generally discussed in terms of the tasks and position of the state, the monopoly of violence, and by referring to constitutional and fundamental legal perspectives. This study shows that international comparative research on (plural) policing cannot be based on the tacit assumption that central concepts such as public good have universal relevance. On the contrary, these normative concepts are highly context dependent, an important conclusion for future international comparative research on policing and security.